Influence of permeable surface resistance of rotating cylinder on the outside flow structure - Юр’єв, Сергій Олександрович (Technology audit and production reserves, 2012)
The paper describes the results of numerical study of the effect of permeable surface resistance on the flow structure in the vicinity of the rotating permeable cylinders. The dependences for the coefficient of uniformity of flow from flow rate and the porous surface resistance are obtained